Nebuchadnezzar and its Relationship with Jews Comparative Study of the Three Divine Religions (Islam, Judaism and Christianity) - Mahmood, Dhuha Adel; nori, Anwar zuheer (Journal of Islamic Sciences, 2019)
Praise be to Allaah and peace and blessings be upon the Messenger of Allah. After this, the reason we chose this subject from the Islamic point of view is because this name is related to the time of the Israelites in Surat Al- Israa in the first and last promise as the general interpreters went to it. Hearing a lot, especially in our beloved homeland as an Iraqi of Arab origin of the sons of Sam Ibn Noah took Babylon as his capital, which is part of our dear country. This is what we proved from many ancient and modern sources after a discussion, some of which show that the lineage of Nebuchadnezzar is due to Ham ’s son Noah, and that Ham is the father of the Persians. Our main findings are: Nebuchadnezzar is of Arab rather than Persian origin Nebuchadnezzar had been converted to Islam because he was influenced by the prophets of the Israelites. Nebuchadnezzar did not treat the Israelites in captivity badly, but provided them with places where they could earn a decent living despite their constant treachery, but wanted to be under constant surveillance. The importance of this subject lies in making a comparison in the mention of this king in the three monotheistic religions to know what is the origin of Nebuchadnezzar and how he ruled and why the captivity and what impact Nebuchadnezzar on the Jews and the influence of Jews and what was his religion and whether he changed it later to be influenced by the prophets of the children of Israel, and is it His promises in the Koran (the promise of the first and the Hereafter) in a neutral scientific manner. The comparative method was used in this study between the three monotheistic religions as well as the historical method which was based on taking from what the three heavenly books indicated a hint or statement, namely the Qur’an, the Torah and the Bible, as well as Hadith books, exegesis books, historical books and some modern books dealing with this subject.